Association between breakfast consumption frequency and the risk of irritable bowel syndrome among Chinese female college students: A cross-sectional study. Issue 41 (15th October 2021) - Zhang, Chaowei; Zhang, Jingyu; Wang, Yaru; Lang, Rui; Su, Linxiu; Yu, Miao; Zhao, Xiaochen; Yang, Guang; Ren, Zhongyu
Abstract : Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder that affects specific groups of people. The relationship between breakfast consumption frequency and the risk of IBS is unclear. This study aimed to investigate the association between breakfast consumption frequency and the risk of IBS among Chinese female college students. In this cross-sectional study (n = 706) conducted in October 2018, the frequency of breakfast consumption was categorized as 0 to 3 times/week, 4 to 6 times/week, or daily. IBS was diagnosed according to the Rome III criteria and was based on the presence of abdominal pain or discomfort for at least 3 months during the previous 6 months, with at least 2 or more of the following conditions: changes in frequency or form of stool and/or decrease in pain after defecation. We adjusted for confounding factors, including age, only child (yes or no), parents' educational levels (senior high school or below, college, or postgraduate), parents' marital status (married, widowed, or divorced), smoking status (smoker or nonsmoker), drinking status (drinker or nondrinker), body mass index, and depressive symptoms. A multiple logistic regression analysis was performed to determine the relationship between breakfast frequency and the risk of IBS. Among 706 participants, 23.7% were the only child in their family, and the proportion of parents divorced or widowed was 18.5%. The proportion of fathers and mothers with high school education or above was 93.3% and 96.3%, respectively. The prevalence of IBS among the participants was 17.3% (122/706). Multivariate logistic regressions analysis showed that breakfast consumption frequency is negatively associated with the risk of IBS after adjusting for confounding factors. The odds ratios (95% confidence intervals) for IBS in the breakfast frequency category of 0 to 3 times/week, 4 to 6 times/week, and daily were 1.00 (reference), 0.96 (0.58, 1.60), and 0.45 (0.26, 0.78), respectively ( P  = .002). Our data revealed that regular breakfast consumption is associated with a lower risk of IBS among Chinese college students. Future cohort and/or interventional studies should be conducted to further explore the association between breakfast consumption frequency and IBS.